Comparison of Fe-enhanced oxygen evolution electrocatalysis in amorphous and crystalline nickel oxides to evaluate the structural contribution. Issue 2 (11th November 2021) - Bak, Jumi; Yun, Tae Gyu; An, Ji-Sang; Bae, Hyung Bin; Chung, Sung-Yoon
Abstract : By comparison between amorphous and crystalline phases, we elucidate that the local structural factor of Fe–O has an impactful contribution to the electronic states of Fe boosting of OER catalytic activity in perovskite-type nickel oxides. Abstract : Control of electronic states is a central issue in electrocatalysis, as it determines the charge transfer behavior for better catalytic reaction efficiency. While a variety of chemical modifications have thus been attempted in many complex oxides to induce a change of electronic states at catalytically active sites, few studies to clarify the influence of local crystal structures on the electronic states under the same composition have been reported. Here we compare the electrocatalysis of the oxygen evolution reaction (OER) between amorphous and crystalline perovskite nickelates in a thin-film form, when Fe is added as an active site. We identify that the improvement of the OER activity by Fe in amorphous films, where the atom arrangement is random, is insensitive to the method of Fe doping. In contrast, an order of magnitude difference in OER activity is induced in crystalline films, strongly depending on the resulting structure variation during doping. Theoretical calculations also consistently show a notable increase in the density of Fe 3d states beneath the Fermi level for exceptionally high activity. Our study demonstrates that the atomic-scale structure in crystalline oxide catalysts should not be overlooked as a key parameter for understanding the enhancement of OER catalysis.